2017
DOI: 10.1007/s00774-017-0842-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased sensory nerve excitation and bone pain associated with mouse Lewis lung cancer in TRPV1-deficient mice

Abstract: Bone pain is one of the most common and life-limiting complications of cancer metastasis to bone. Although the mechanism of bone pain still remains poorly understood, bone pain is evoked as a consequence of sensitization and excitation of sensory nerves (SNs) innervating bone by noxious stimuli produced in the microenvironment of bone metastases. We showed that bone is innervated by calcitonin gene-related protein (CGRP) SNs extending from dorsal root ganglia (DRG), the cell body of SNs, in mice. Mice intratib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…Interestingly, the levels of tumour‐infiltrating neutrophils and eosinophils, as well as sensory neuron innervation, correlate with the severity of pain and itch experienced by patients with melanoma . Finally, the pharmacological inhibition and genetic depletion of TRPV1 + neurons support an essential role in these fibres in transmitting bone cancer‐induced pain. Thus, in a mouse model of this disease, blocking CB2R dampens morphine tolerance .…”
Section: Endogenous Triggersmentioning
confidence: 95%
“…Interestingly, the levels of tumour‐infiltrating neutrophils and eosinophils, as well as sensory neuron innervation, correlate with the severity of pain and itch experienced by patients with melanoma . Finally, the pharmacological inhibition and genetic depletion of TRPV1 + neurons support an essential role in these fibres in transmitting bone cancer‐induced pain. Thus, in a mouse model of this disease, blocking CB2R dampens morphine tolerance .…”
Section: Endogenous Triggersmentioning
confidence: 95%
“…19 Since the newer TRPV1 antagonist(s) were not commercially available during the execution of our experiments, we used an older (less specific) TRPV1 antagonist peptide called L-R 4 W 2 to determine the therapeutic potential of TRPV1 antagonism in our model. To diminish any potential systemic side effects of L-R 4 W 2 , the TRPV1 antagonist was delivered intraurethrally into the prostate of mice with established pelvic tactile allodynia at days 20,22,24,26,28,30,32, and 34 ( Figure 6A). Notably, our data confirmed that treatment with L-R 4 W 2 reversed the level of pelvic tactile allodynia in mice with EAP after initial infusion at day 20 ( Figure 6B).…”
Section: Trpv1 Antagonist Blunts Persistent Pelvic Tactile Allodyniamentioning
confidence: 99%
“…Despite the mixed research results on TRPV1 compounds, studies have demonstrated that TRPV1‐deficient mice show decreased pain in models of arthritis, bone cancer, and inflammatory bowel disease . However, it is unclear whether TRPV1 plays a role in the mouse model of CP/CPPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, C Opioid is a mainstay treatment for cancer pain, which often becomes unbearable after tumor metastasis to bone tissue 15 . We assessed whether morphine would attenuate cancer pain in WT and KO mice in bone cancer pain 16 . Inoculation of Lewis lung cancer cells into tibia resulted in severe cancer pain, as indicated by reductions in mechanical and thermal pain thresholds.…”
mentioning
confidence: 99%